Persepsi, Prospek Kerja, Lapanga PERSEPSI MAHASISWA PENDIDIKAN GEOGRAFI FIS UNIMED TERHADAP PROSPEK KERJA BAGI LULUSAN JURUSAN PENDIDIKAN GEOGRAFI - Mindo Sihite (Jurnal Teknologi Informasi, 2023)
This study aims to determine the perceptions of UNIMED FIS Geography Education students on job prospects for graduates of the Geography Education Department and the tendency of UNIMED FIS Geography Education students who wish to become teachers and non-teachers based on their region of origin, socio-economic profile, and specialization. The research method used is descriptive qualitative method. The data collection technique in this study was by collecting primary data through online questionnaires using Google forms and collecting secondary data by searching for data through books, journals, articles, the internet, and other official documents that can assist this research. The data analysis technique is carried out through the stages of editing, coding, tabulating, calculating percentages, analyzing data, and making conclusions.The results of this study indicate that: (1). Student perceptions of job prospects for geography education graduates are in the opportunity category, with a final percentage score of 75.09%. (2). The tendency of UNIMED FIS Geography Education students who wish to become teachers and non-teachers: (a). Based on regional origin, of the 117 students who became respondents came from 31 districts/cities, 40 (34.18%) students wished to become teachers and 77 (65.82%) students wished to be non-teachers. (b). Based on socio-economic conditions, students tend to choose the teacher's field of work because the field of work has a good social status or assessment in the community. From an economic point of view, students stated that their parents' economic income and cheaper education costs were a consideration in choosing a field of education. (c). Based on the field of student specialization, the highest percentage was in the social field, namely 41.8% or as many as 49 students. The second place is in the field of Education CBC with a percentage of 23.1% or as many as 27 students. Then in third place is the physical KBK field, namely 18% or as many as 21 students. KBK with the lowest percentage is in the field of Engineering KBK with a percentage of 17.1% or as many as 20 students. Students' perceptions of scientific field groups are also related to how students choose the field of work they will choose.